Blood-based novel biomarkers for nonalcoholic steatohepatitis. (1st May 2018) - Qiu, Yun; Wang, Sufan; Wan, Ting; Ye, Mingtong; Jiang, Rui; Pei, Lei; Yang, Lili
Nonalcoholic fatty liver disease has become a social health challenge of global concern. The term nonalcoholic steatohepatitis (NASH) is a more severe condition than simple steatosis and distinguishing NASH from nonalcoholic fatty liver disease is particularly important. Liver biopsy remains a gold standard in diagnosing NASH. Meanwhile, radiological techniques such as ultrasonography and MRI are also applied widely. However, the invasive and expensive examination is not suitable for screening, and there is a great need for reliable and appropriate biomarkers to screen patients for NASH. Based on the current studies of blood-based novel biomarkers, we attempt to summarize the latest findings on biomarkers for NASH, including blood biomarkers encompassing proteins, lipids and miRNAs; the correlation between extracellular vesicles and NASH; and treatment strategies for NASH.